2003
DOI: 10.1149/1.1624842
|View full text |Cite
|
Sign up to set email alerts
|

Optical Analyses (SE and ATR) and Other Properties of LPCVD Si[sub 3]N[sub 4] Thin Films

Abstract: Thin silicon nitride films ͑less than 20 nm͒ deposited on ͑100͒ silicon substrates via low pressure chemical vapor deposition ͑LPCVD͒ at three temperatures ͑730, 760, and 825°C͒ were analyzed by spectroscopic ellipsometry ͑SE͒, attenuated total reflection ͑ATR͒, and other tools. Films appeared to have similar optical bandgaps ͑ϳ5 eV͒, and the values decreased slightly with the higher deposition temperature. Second ionic mass spectroscopy results showed that a similar amount of oxygen exists in the interface be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Alternatively, the pre-adsorption reactions in the case of PA-CVD or PE-CVD could produce more active reactant species, leading to higher surface reaction rates at shorter surface diffusion lengths, potentially producing less contaminated SiN x films but with poorer step coverage and lower etch resistance. 107 Although a significant body of research in thermal CVD SiN x can be found in the literature prior to 2010, 73,105,106,[111][112][113][114][115] there are very few recent reports (within the last five years) on the topic, due most likely to the high thermal budget required for dissociation and reaction of the Si and N chemistries, except for 34 included the use of pulsed RF generated by modulating a continuous 200Hz low-frequency wave signal generator with 50% duty cycle in the PE-CVD reaction of SiH 4 and NH 3 at 150…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the pre-adsorption reactions in the case of PA-CVD or PE-CVD could produce more active reactant species, leading to higher surface reaction rates at shorter surface diffusion lengths, potentially producing less contaminated SiN x films but with poorer step coverage and lower etch resistance. 107 Although a significant body of research in thermal CVD SiN x can be found in the literature prior to 2010, 73,105,106,[111][112][113][114][115] there are very few recent reports (within the last five years) on the topic, due most likely to the high thermal budget required for dissociation and reaction of the Si and N chemistries, except for 34 included the use of pulsed RF generated by modulating a continuous 200Hz low-frequency wave signal generator with 50% duty cycle in the PE-CVD reaction of SiH 4 and NH 3 at 150…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…Alternatively, the pre-adsorption reactions in the case of PA-CVD or PE-CVD could produce more active reactant species, leading to higher surface reaction rates at shorter surface diffusion lengths, potentially producing less contaminated SiN x films but with poorer step coverage and lower etch resistance. 107 Although a significant body of research in thermal CVD SiN x can be found in the literature prior to 2010, 73,105,106,[111][112][113][114][115] there are very few recent reports (within the last five years) on the topic, due most likely to the high thermal budget required for dissociation and reaction of the Si and N chemistries, except for 284 * The table is intended to provide baseline comparisons of bond dissociation energies of selected organic and inorganic Si and N source chemistries with the most commonly used precursors. 102,103 generator with 50% duty cycle in the PE-CVD reaction of SiH 4 and NH 3 at 150 • C. The process yielded film densification (over 20% increase in film density) and smoothing (a decrease in average surface grain size standard deviation from 0.2nm 2 to 0.04nm 2 ), with the SiN x films exhibiting smoother surface morphology and lower void density.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%